Evaluating Sururu shell waste (Mytella falcata) as an eco-friendly recycled aggregate in mortar production - Cardoso, Ariane da Silva; Kohlman Rabbani, Emilia Rahnemay; Silva, Alison Lopes da; Sá, Mattheus Karryery Coelho R. G. de; Monteiro, Eliana Barreto; Shakouri, Mahmoud (Frontiers in Built Environment, 2024)
Improper disposal of mollusk shells has led to environmental issues worldwide. Given their primary composition of calcium carbonate, these shells have been studied for their potential use as aggregate in cement composites, offering an environmentally appropriate destination for the waste and reducing virgin raw material use. However, there is a lack of research on the application of Sururu (Mytella falcata) shells, a species of mollusk commonly fished in countries such as Brazil. This study investigated the effects of Sururu shells waste from a Brazilian region on the mechanical and physical properties of mortar when partially replacing natural fine aggregate. Three mortar mixtures were produced, replacing 10, 20, and 40% of natural sand with Sururu shell aggregate (SSA) by mass. The specimens underwent consistency and density tests in their fresh state, and compressive strength, dynamic modulus of elasticity, and capillary absorption tests in their hardened state. The results showed that workability decreased with the increase in SSA replacement, resulting in a reduction of 31.5% in consistency at 40% SSA replacement level. Compressive strength also decreased with SSA incorporation, but all samples continued to gain strength after 28 days, with 10% SSA samples showing only a 2.7% reduction compared to the control specimens. The dynamic modulus of elasticity was minimally impacted at 10% SSA, but significantly reduced at higher levels. Notably, SSA reduced capillary absorption in samples after 24, 48, and 72 hours, indicating potential benefits in moisture management. It was concluded that replacing 10% of natural sand with SSA was the most suitable option, considering the investigated mechanical properties of the mortar produced with SSA. However, further research is recommended to examine the durability and environmental impact of this solution.